2010
DOI: 10.1111/j.1438-8677.2009.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome size dynamics in Artemisia L. (Asteraceae): following the track of polyploidy

Abstract: Polyploidy is a key factor in the evolution of higher plants and plays an important role in the variation of plant genomes, leading to speciation in some cases. During polyploidisation, different balancing processes take place at the genomic level that can promote variation in nuclear DNA content. We estimated genome size using flow cytometry in 84 populations of 67 Artemisia species and one population of Crossostephium chinense. A total of 73 sequences of nrDNA ITS and 3'-ETS were newly generated and analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 65 publications
2
58
2
Order By: Relevance
“…The hypothesis that the B genome is smaller than the A genome was put forward by Iiyama and Grant (1972) for this reason, although this was also in support of a proposed AABBDD genome constitution for the hexaploid, which has been subsequently rejected. Polyploid genome downsizing has been observed in most angiosperms, and it is assumed to be a general trend (Kellogg and Bennetzen 2004;Pellicer et al 2010a). The mechanisms leading to loss of the DNA in polyploids include unequal homologous recombination (Bennetzen et al 2005), non-homologous recombination (Devos et al 2002), general elimination of redundant DNA (Ozkan et al 2003;Leitch and Bennett 2004), and specific elimination of duplicate genes (Renny-Byfield and Wendel 2014; Evans et al 2015).…”
Section: Genome Size Reduction After Polyploidizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that the B genome is smaller than the A genome was put forward by Iiyama and Grant (1972) for this reason, although this was also in support of a proposed AABBDD genome constitution for the hexaploid, which has been subsequently rejected. Polyploid genome downsizing has been observed in most angiosperms, and it is assumed to be a general trend (Kellogg and Bennetzen 2004;Pellicer et al 2010a). The mechanisms leading to loss of the DNA in polyploids include unequal homologous recombination (Bennetzen et al 2005), non-homologous recombination (Devos et al 2002), general elimination of redundant DNA (Ozkan et al 2003;Leitch and Bennett 2004), and specific elimination of duplicate genes (Renny-Byfield and Wendel 2014; Evans et al 2015).…”
Section: Genome Size Reduction After Polyploidizationmentioning
confidence: 99%
“…However, genome size can vary over several orders of magnitude in eukaryotes (Bennett and Leitch 2005;Pellicer et al 2010a). In Angiosperms, 2C values range from 0.13 pg in Genlisea aurea (Greilhuber et al 2006) to 304.4 pg in Paris japonica (Pellicer et al 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…This increased per-cell nuclear DNA content, however, does not necessarily translate into higher whole-organism P concentration. For one, polyploids often have larger (and fewer) cells (Fankhauser, 1945;Benfey, 1999;reviewed in Mable, 2004), and smaller haploid genomes (Ozkan et al, 2003;Leitch and Bennett, 2004;Murray et al, 2005;Gerstein et al, 2006;Eilam et al, 2010;Pellicer et al, 2010) relative to closely related taxa with lower ploidy. In addition, variation in RNA content may have more of an effect than variation in DNA content on body P content because RNA (1) makes up a substantial fraction of organismal biomass (415% dry mass in some animals and 440% dry mass in bacteria; Elser et al, 1996Elser et al, , 2003 and (2) varies considerably among taxa (for example, %RNA ranges from o1% to 413% dry mass in zooplankton (Gillooly et al, 2005)).…”
Section: Polyploidy and Organismal Phosphorus Economicsmentioning
confidence: 99%
“…Samples were subsequently stained with PI to a final concentration of 60 µg/mL (Sigma-Aldrich Química), kept on ice for 20 min, and measured in an Epics XL flow cytometer (Coulter Corporation). Further technical details regarding the procedure can be found in Pellicer et al (2010b). Measurements were carried out at the Scientific and Technological Centers, University of Barcelona.…”
Section: Genome Size Estimationsmentioning
confidence: 99%
“…The distribution pattern of annual species confirmed that these taxa were concentrated in the earlier branches of the tree, whilst the core of the subgenera Artemisia, Pacifica, Seriphidium, and Tridentatae, which are late-branched, completely lacked annual representatives (Figure 1 . annua, A. leucodes, A. magellanica, A. scoparia, and A. tournefortiana (Torrell and Vallès, 2001;Garcia et al, 2004;Pellicer et al, 2010b). Genome sizes varied ca.…”
Section: Phylogenetic Placement Of Annual Artemisiamentioning
confidence: 99%